Analysis Of Income Tax Article 21 And Income Tax Article 4 Paragraph (2) And Income Tax Article 26 To Calculate Employees Salaries In Companies - Farina Jessen Yap (International Journal of Economics and Management Research, 2023)
One of the largest state revenues is from the tax sector. In connection with the description above, one type of tax that is emphasized in this study is income tax, especially in income tax article 21, income tax article 4 paragraph (2) and income tax article 26. The formulation of the problem in this study is to determine whether Company employees have calculated, deducted, deposited and reported income tax article 21, income tax article 4 paragraph (2) and income tax article 26 in accordance with the applicable tax regulations. The method used in this study is descriptive approach, this type of research is descriptive qualitative and the nature of this research is explanatory research. The population and sample in this study is a list of salary data for 30 employees for the period 2019. The data collection method was carried out by literature study, interviews and documents. The data analysis technique used in this research is descriptive analysis. The results showed that there were still employees who did not report income tax article 21, income tax article 4 paragraph (2) and miscalculate income tax article 26 due to lack of information about income tax.